The function of "weeping and gnashing of teeth" in Matthew's gospel - Zoltan L. Erdey; Kevin G. Smith (Acta Theologica)
On six occurrences (8:12; 13:42; 13:50; 22:13; 24:51; 25:30), Matthew recorded Jesus pronouncing judgment, using the idiom “weeping and gnashing of teeth”. Each occurrence played a central role in the development of Matthew’s theology, by communicating not only a fundamental component of the theme of judgment, but also an increasing force and potency of the event itself. It was discovered that the phrase may have four possible functions, namely (a) a system by which Matthew hoped to make the message of the particular passage unforgettable; (b) a prophetic anticipation of an aspect of the larger shape of history; (c) a linguistic device to increase the degree of emphasis or heighten the force given to the message of eschatological judgment; and (d) a literary connector holding together a number of specific passages of Scripture. In Matthew’s case, the phrase glues together the passages that communicate a holistic theology of end-of-time judgment.